Home security system / Mohamad Zul Husni Mohammad Nazri & Muhammad Syahran Ismail - Mohammad Nazri, Mohamad Zul Husni; Ismail, Muhammad Syahran (2015)
This is a digital home security system which can monitor motion sensor, magnetic switch (windows & doors). The goal of this project is to utilize the after-market parts and build an integrated home security system. This system also has alarm. Hence the security system will sound an alert when there is an attempt of break-in. Furthermore this will be the lowest cost security system within all security system that already exists. So that all place that needs to be secure have our security system. The place had installed the system will in good condition and secure